Desenvolvimento de plantas de milho que expressam Jaburetox visando resistência a lepidópteros-praga - Didoné, Dielli Aparecida (2018)
Numerous studies of genetic engineering and genetic improvement have been carried out with this cereal and the Agrobacterium tumefaciens preferred technique for gene transfer. However, this technique requires a transformation and regeneration plant system adjusted since the gene is generally introduced to the level of totipotent cells which gives rise to whole, fertile plants. The experiment reported in this paper is devoted to examine the in vitro regeneration capacity and the genetic transformation of immature zygotic embryos of maize via A. tumefaciens. In the first part are reported experiments evaluating the regenerative capacity of the H3MT-2 hybrid of maize and the adaptation and optimization of plant regeneration from Hi-II genotype in the LBV-UPF. The second part reports the transient expression of immature zygotic embryos of the variety BR 451 and the hybrid Hi-II transformed with A. tumefaciens at different periods and temperatures of co-cultivation. yo verify the ideal time to perform the GUS histochemical assay after infection to access the frequency of transient transformation. As results, it was observed that the pre-regeneration step proved to be crucial in plant regeneration of Hi-II genotype. For this genotype, the pre-regeneration medium containing 0.25 mg.L-12,4-D was shown to be more effective in the conversion of somatic embryos into plants (410 plants from the initial 2.5 g of embryogenic callus) and also accelerated the regeneration process in two weeks. The addition of ABA fitorregulatores with 2,4-D resulted in an increase in cell division, delaying the onset of development of plants 15 days. The H3MT-2 genotype did not respond positively to treatment and regenerationsystem used in this experiment. It has been shown in this work the optimization of in vitro regeneration of maize Hi-II genotype that can result in acceleration and efficiency of the production of genetically modified plants. The completion of the histochemical GUS assay after five days of infection allows for better access the transient transformation than after three days. For both genotypes of maize HiII and BR 451, the transfer of the T-DNA by the bacterium was enhanced by co-culture of immature embryos for five days at 20 °C, since it resulted in a higher number of blue spots per somatic embryos, 21.4 and 23.1, respectively. It was possible to transfer the bar marker gene in 0.39% of the embryos from Hi-II genotype infected with A. tumefaciens and the calli that carried the bar gene were obtained from co-culture temperature of 20°C. It was possible to optimize transient transformation for the two genotype studied.